Flood sediments as a source of replenishment of alluvial soils with plant nutrition elements - A. V. Ilinskiy; K. N. Evsenkin; A. A. Pavlov (Аграрная наука Евро-Северо-Востока, 2024)
Flood sedimentation in conditions of regular floodplain flooding is a key factor in the formation of alluvial soil.  The nature of the passage of hollow waters and their composition affect the quantitative and qualitative characteristics of flood sediments, while having a significant impact on the agroecological state of the floodplain agricultural landscape. The aim of the research was to study the role of flood sediments in enriching the underlying alluvial soil with nutrients. The experiment was conducted on reclaimed arable lands of the Ryazan region in 2023. Determination of the sediment load level and sampling on the surface were carried out using plastic sedimentation samplers fixed on the soil surface, located at a distance of 200 m from each other. The installation was carried out on March 23, the duration of sediment collection was 42 days before the descent of the hollow waters. The average sediment load level of 15.4 t/ha was established, the agrochemical properties of flood sediments and underlying soil were studied, the structure of organic matter, macro– and microelements with flood sediments and their removal from the corn harvest to silage was analyzed. Together with sediments the soil received (kg/ha): total nitrogen – 107.80, total phosphorus – 43.10, total potassium – 104.70, organic matter – 2464,0, mobile phosphorus 15.20, exchangeable potassium 17.80; trace elements (g/ha): boron – 11.86, molybdenum – 1.54, zinc – 122.74, manganese – 1215.06, copper – 200.20, cobalt – 52.05. With a corn harvest for silage of 36.1 kg/ha, the takeaway was: N – 105 kg/ha, P2O5 – 33 kg/ha,  K2O – 105 kg/ha. The conducted studies indicate the undoubted agronomic value of flood sediments, they can partially meet the need for fertilizers, therefore, it is necessary to take into account the mass of the substances used to carry out appropriate adjustments to the fertilizer application system. In 2023, the mass of incoming substances with flood sediments completely covered the need for nitrogen; for mobile phosphorus the need decreased to 17.8 kg/ha, for exchangeable potassium the need decreased to 87.2 kg/ha.